EP-213 An Audit on the Initial Management of Acute Cholecystitis: A Single Centre Experience. (9th August 2022) - Stoll, Sarah; Doherty, Rachel; Sedighi, Tina; Davidson, Christopher; Modi, Hemel
Abstract: Aim: Acute cholecystitis (AC) accounts for up to one third of emergency surgical admissions. The initial management of AC includes fluid resuscitation and appropriate antibiotic therapy. The aim of this study is to audit compliance with local microbiology guidelines for the treatment of AC and to develop interventions that improve compliance rates. Method: All patients admitted from September to December 2020 with radiologically confirmed AC were included in an initial prospective audit (n=39 patients). Antibiotic prescriptions, patient demographics, presence of fever (>38°C), inflammatory markers and liver function tests were recorded. The results were disseminated, educational material produced, and antibiotic "champions" appointed to improve adherence to antibiotic guidelines. A prospective re-audit was conducted from May to June 2021 to establish the effectiveness of the interventions (n=49 patients). Compliance rates before and after the interventions were compared using a Chi-squared test. Binomial logistic regression was carried out to establish whether any patient demographic or clinical parameters were independent predictors of prescribing behaviour. Results: Compliance to antibiotic guidelines for AC significantly improved following the interventions (12.8% vs 57.1%; p<0.001). Age, gender, temperature, inflammatory markers and liver function tests were comparable in both groups and were not found to be independent predictors of non-compliant antibiotic prescription. Conclusions: Adherence to antibiotic guidelines for AC can be improved with educational interventions and the appointment of individuals responsible for ensuring correct prescribing behaviour. Interestingly, patient demographics, signs of sepsis or liver function did not influence prescribing behaviour, suggesting that divergence from antibiotic guidelines may be due to ingrained prescribing dogma.